Influence of the addition sequence of PVA-fibers and water on mixing and rheological behavior of mortars - França,M. S. de (2016)
ABSTRACT The mixing process of fiber-containing cementitious suspensions is a crucial factor to obtaining a good dispersion of fibers and guarantee adequate mechanical performance of the hardened products. The addition of fibers into the suspension causes reduction of the fluidity of the system due to factors inherent to the fibers, the matrix and their interaction. During mixing, these interactions make dispersion and homogenization processes more difficult due to the formation of fibers - particles agglomerates. Conventional techniques to assess workability of mortars are inadequate to evaluate the rheological behavior of fiber-reinforced systems, in which parameters like viscosity and yield stress are not completely taken into account. Therefore, this work employs rotational rheometry to evaluate the influence of fiber and water addition sequences on mixing and rheological behavior of mortars containing Polyvinyl Alcohol (PVA) fibers. Constant test parameters were: mixing time of 317s; impeller velocity 126.5 rpm; water flow 128g/s. A constant mix design was used with a water content of 16%wt, and a 0.2%vol of fibers were added to the reference composition. Four mixing sequences were studied: S1 and S2 are based on the addition of fibers at different stages of the mixing process; while in S3 and S4 not only the fibers are added at different stages, but also the water addition is performed in two steps (25% first and 75% latter).Results showed that it is possible to optimize the mixing step of fiber-containing systems by changing the moment of fiber addition into the mixture. The introduction of fibers after mixing the dry mortar with water, when it already had achieved its fluidity point, demanded a lower mixing effort and produced a more flowable material.